Polyaniline as a potential adsorbent for the removal of methylene blue in aqueous solution - Nur Amira, Muhammad Rosli (2015)
In industrial pollutants, dyes are one of the most essential especially in textile, plastics, paper, leather and many other industries. Various ways have been proposed in order to remove color of dyes. Therefore, adsorption process is more acceptable and effective way to remove the dyes from wastewater as the process provides an attractive alternative for the treatment of colored water. In this work, the prepared polymerization nanoparticle of polyaniline as adsorbent is applied in order to remove the methylene blue dye. The adsorption studies such as effect of contact time, initial dye concentration, adsorbent dosage and pH were considered. Several adsorption kinetics including pseudo-first order and pseudo-second order were used to investigate the mechanism of the adsorption process. Apart from that, equilibrium data was fitted on to Langmuir and Freundlich models. The percentage removal of methylene blue was enhanced with increasing contact time, initial dye concentration, adsorbent dosage and pH. The percentage removal of methylene blue is strongly affected by pH of polyaniline, which the optimum pH was at 5.0. Regarding to Langmuir model, the qmₐₓ, for adsorption of methylene blue was 333.33 mg/g. The pseudo-first order and Langmuir isotherm model had the best fitness which the R² values were 0.501 and 0.988, respectively. The study has demonstrated that the polyaniline was considerable i potential to become low cost and eco-friendly adsorbent, hence it can be utilized commercially for the removal of methylene blue dye or selected dyes from aqueous solution.